Fractinations of Coconut Oil from Coconut Milk and Antibacterial Activities - Su'i, Moh.; Sumaryati, Enny; Dwi Anggraeni, Frida; Prasetyo, Ricky (International Journal of Engineering and Technology, 2019)
Hydrolysed coconut oil contained of free fatty acid (FFA fraction), monoglyceride, diglycerides, and triglycerides (glycerides fraction). Free fatty acid (lauric acid, caprylic acid, capric acid) and monoglyceride (monolaurin, monocaprin, etc) had antibacterial activity. Triglycerides and diglycerides had none antibacterial activity. This research was studied about which fraction that had most excellent antibacterial activity. It was prepared in two stages : the first step was fractination of coconut oil and the second step was tested of antibacterial activity. Antibacterial test were carried out with dilution method. The media contained of bacteria (Bacillus stearothermophillus, Salmonella sp., E. Coli, and Staphylococus aureus) was added by coconut oil fractions (unhydrolysed coconut oil, hydrolysed coconut oil, free fatty acids and glycerides fraction) with varying concentrations (0 to 12.5%). All fractions were tested antibacterial activity against Bacillus stearothermophilus. Furthermore, only two fractions (free fatty acids and glycerides fraction) were tested antibacterial activity against Salmonella sp., E. Coli, and Staphylococus aureus bacteria. The results revealed that free fatty acids fraction with 6.25% (w/v coconut oil) could inhibit Bacillus stearothermophilus bacteria. While, unhydrolysed coconut oil, hydrolysed coconut oil and glycerides fraction could not able to inhibit the Bacillus stearothermophilus bacteria up to 12.5%. Free fatty acids and glycerides fractions with 3.13% (w/v coconut oil) could inhibit Salmonella sp. and Staphylococcus aureus bacteria. Whereas, the E. Coli bacteria could be inhibited by free fatty acids fraction with 3.13% (w/v coconut oil) and glycerides fraction with 6.25% (w/v coconut oil).Â Â